Asafetida plant extract as potential antioxidant, antimicrobial, and odor retardant insecticidal agent against Culex pipiens - Nirvina Abdel Raouf Ghazawy; Ibrahim Taha Radwan; Hattan S. Gattan; Mohammed H. Alruhaili; Mohamed M. Baz; Eman Alaaeldin AbdelFattah; Abadi M. Mashlawi; Abdelfattah Selim (Scientific Reports)
Abstract Hundreds of species of mosquitoes are reported to be capable of transmitting diseases to humans. As a result, mosquito control is essential worldwide, especially in locations with large concentrations of freshwater sources. Asafetida plant extract was prepared and studied their phytochemical characteristics to be used as insecticidal agent against c. pipiens. The total carbohydrate contents, polyphenolic contents, flavonoid contents and protein contents were found 51.90, 129.0, 10.27, and 366.67 mg/g, respectively. The greatest mortality percentage was observed at the concentration 1000 ppm (86.7%) and (80%) after 12 h and 24 h post treatment. In respect to the mortality rate the LC 50, LC 90 and LC 95 were found to be 352.1, 3154.8 and 4028.8 ppm. The total antioxidant values were significantly higher at the concentrations of 125 ppm and 1000 ppm (1.52, 1.49) through the first 12 h of the treatment as well as lipid per oxidation levels showed higher enzymatic levels of 3.6, 3.7 at 125, 250 ppm than those of the control group (0.11).The phenolic concentration increased gradually from 0 to 250 ppm ( 0.32, 1.32) then suppressed to (0.58) at 500 ppm. DPPH levels showed noticeable elevation through 12 h were (97.0) at 125 ppm while declined at 250 ppm till (95.6) to rise again at 500 ppm (97.3). SOD gradually increase at 500 ppm at 12 and 24 h (0.37, 0.36) than control while superoxide anion radical concentration levels presented as fluctuated from 0 to 1000 ppm.